TRENDS IN THE DIGITAL TRANSFORMATION OF UNIVERSITIES AND DIGITAL ACTIVATORS OF CHANGE - Наталія Бобро (Економіка та суспільство)
The article examines key aspects of the digital transformation of universities in the context of the increasing role of information and communication technologies in shaping a new educational architecture. It justifies the need to revise traditional models due to technological progress, global competition, and growing stakeholder expectations. The concept of a digital university is presented as an institutional form that ensures flexibility, openness, personalization, and efficiency. Special focus is placed on digital activators, particularly digital avatars, which act as virtual agents of participants, enabling adaptive learning management, automated feedback, and role replication. A generalized model of a digital avatar as a complex socio-technological object is proposed, along with scenarios for university development based on digital maturity and institutional capacity. The results can be applied in shaping digital strategies, modernizing management, and creating personalized educational environments.